Response of downy oak (Quercus pubescens Willd.) to climate change: transcriptome assembly, differential gene analysis and targeted metabolomics - Mevy, Jean-Philippe; Loriod, Beatrice; Liu, Xi; Corre, Erwan; Torres, Magali; Büttner, Michael; Haguenauer, Anne; Reiter, Ilja Marco; Fernandez, Catherine; Gauquelin, Thierry (Plants, 2020)
Global change scenarios in the Mediterranean basin predict a precipitation reduction within the coming hundred years. Therefore, increased drought will affect forests both in terms of adaptive ecology and ecosystemic services. However, how vegetation might adapt to drought is poorly understood. In this report, four years of climate change was simulated by excluding 35% of precipitation above a downy oak forest. RNASeq data allowed us to assemble a genome-guided transcriptome. This led to the identification of differentially expressed features, which was supported by the characterization of target metabolites using a metabolomics approach. We provided 2.5 Tb of RNASeq data and the assembly of the first genome guided transcriptome of Quercus pubescens. Up to 5724 differentially expressed transcripts were obtained; 42 involved in plant response to drought. Transcript set enrichment analysis showed that drought induces an increase in oxidative pressure that is mitigated by the upregulation of ubiquitin-like protein protease, ferrochelatase, oxaloacetate decarboxylase and oxo-acid-lyase activities. Furthermore, the downregulation of auxin biosynthesis and transport, carbohydrate storage metabolism were observed as well as the concomitant accumulation of metabolites, such as oxalic acid, malate and isocitrate. Our data suggest that early metabolic changes in the resistance of Q. pubescens to drought involve a tricarboxylic acid (TCA) cycle shunt through the glyoxylate pathway, galactose metabolism by reducing carbohydrate storage and increased proteolytic activity.
Gesehen am 03.12.2020